Madrasah Head's Strategy on Independent Implementation of Changing the Independent Curriculum - Rahmi Nurul Najma; Wahira, Wahira (International Journal of Education, Vocational and Social Science, 2024)
This study explores the strategies employed by madrasah heads in implementing the Independent Curriculum Change at MAN 1 Soppeng, an area previously unexplored in research on religious schools. Using a qualitative approach, the study identifies three key strategies: (1) conducting regular webinars via the Ministry of Religion's Smart Platform, (2) fostering learning communities through MGMP (Subject Teacher Deliberation) and FGD (Focus Group Discussion) activities, and (3) organizing Independent Curriculum Implementation (IKM) workshops. To facilitate the Independent Curriculum Change, the madrasah head established a Madrasah SOP Preparation Team (Standard Operating Procedures). Additionally, a Curriculum Development Team was formed to support the Pancasila and Rahmatan Lil Alamin Student Profile Strengthening Project (P5RA). This team designed activities based on established guidelines, tailored to students' abilities, and collaborated with various stakeholders to ensure success. The study also highlights both supporting and inhibiting factors in the implementation process. Therefore, the madrasah head must adopt effective strategies to successfully manage the transition to the Independent Curriculum.